Prevalence, Attitudes, and Practices of Sports Nutritional Supplementation among Ghanaian University Athletes: A Descriptive Analysis - AKESSEH ARTHUR, Neeyi; KLUBOITO, Yayra (African Journal of Nutrition and Dietetics, 2025)
Nutritional supplementation has become increasingly prevalent among athletes worldwide, with growing interest in its potential to enhance performance, recovery, and overall health. This study investigated the prevalence, attitudes, and practices surrounding sports nutritional supplementation among Ghanaian university athletes. Using a quantitative cross-sectional design, data were collected via structured questionnaires from 446 student-athletes (52.5% male, 47.5% female) across multiple universities during the 2025 Ghana University Sports Association (GUSA) Games. Descriptive statistics were employed to analyze supplement usage patterns, motivations, information sources, and safety perceptions. The results revealed that 62.3% of athletes used supplements, primarily multivitamins (48.9%) and protein powders (34.9%), though 73% consumed them only occasionally. While 49.3% read supplement labels, only 27.7% consistently consulted healthcare professionals, with many relying on friends/family (38.1%) for information. Coach recommendations (55.4%) were the primary motivator, yet 86.8% expressed limited confidence in supplement safety, and 56.5% reported uncertainty about efficacy. Supplement use among university athletes was prevalent, with most favoring multivitamins and protein products. While many athletes practice caution by checking labels and consulting professionals, many rely on non-expert advice, reflecting significant uncertainty about supplement safety and effectiveness. These findings underscore the urgent need for comprehensive nutrition education and professional guidance to promote informed supplement use and protect athlete health. Future research should explore demographic variations in supplement practices and evaluate the effectiveness of educational interventions.